2018
DOI: 10.1111/srt.12438
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the number of enlarged pores according to site, age, and sex

Abstract: The number of enlarged pores differs depending on body site and increased with age. The enlarged pore counts correlate with wrinkle severity and the correlation varies depending on the body site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Results also show that regardless of the variations in density of pores in the different ethnic groups we studied, 15 an increased pore density correlates with the presence of enlarged pore. Another parameter that was also known to be associated with enlarged pore is the elongation of pores 16‐18 . Even if we did not study the age‐related increased elongation of enlarged pores, we show that a strong correlation exists between more elongated shapes and the enlargement of pores.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Results also show that regardless of the variations in density of pores in the different ethnic groups we studied, 15 an increased pore density correlates with the presence of enlarged pore. Another parameter that was also known to be associated with enlarged pore is the elongation of pores 16‐18 . Even if we did not study the age‐related increased elongation of enlarged pores, we show that a strong correlation exists between more elongated shapes and the enlargement of pores.…”
Section: Discussionmentioning
confidence: 68%
“…Another parameter that was also known to be associated with enlarged pore is the elongation of pores. [16][17][18] Even if we did not study the age-related increased elongation of enlarged pores, we show that a strong correlation exists between more elongated shapes and the enlargement of pores. Finally, enlarged pores show a higher colour difference with neighbouring skin than normal pores.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, we found out that as pores getting more obvious, furrow length decreasing, furrow width becoming larger, and small closed polygons merging into large ones, the skin is seen rougher than before. Jung HJ et al, 16 also performed that pore counts increased with age and the increment was huge between 30s and 40s years, while there is no significant difference by gender. Lee SJ et al, 17 reviewed the major causes of pores enlargement, which includes high sebum excretion, decreased elasticity around pores and increased hair follicle volume.…”
Section: Discussionmentioning
confidence: 90%
“…Aging and its associated collagen modifications reduce tissue remodeling by matrix metalloproteinases and decrease the structural and mechanical integrity of collagen fibers 28 . It was assumed that pores would be more noticeable with older age as they become larger and deeper 8,29 . With age, collagen breaks down, causing skin to lose its elasticity.…”
Section: Discussionmentioning
confidence: 99%
“…7 The therapeutic approaches used to treat this problem include topical retinoids, chemical peeling, intense pulsed light and systemic treatments, such as isotretinoin and oral contraceptives; however, their effects in different cases are variable. 8 Moreover, certain therapies may lead to pronounced adverse effects, such as the teratogenic effect of oral isotretinoin as well as the hypercoagulability and breast tenderness caused by oral contraceptives. 9 The used treatment options were generally safe and well tolerated in all cases.…”
Section: Discussionmentioning
confidence: 99%